A multiscale functional map of somatic mutations in cancer integrating protein structure and network topology - Yingying Zhang; Alden K. Leung; Jin Joo Kang; Yu Sun; Guanxi Wu; Le Li; Jiayang Sun; Lily Cheng; Tian Qiu; Junke Zhang; Shayne D. Wierbowski; Shagun Gupta; et al. (Nature Communications)
Abstract A major goal of cancer biology is to understand the mechanisms driven by somatically acquired mutations. Two distinct methodologies—one analyzing mutation clustering within protein sequences and 3D structures, the other leveraging protein-protein interaction network topology—offer complementary strengths. We present NetFlow3D, a unified, end-to-end 3D structurally-informed protein interaction network propagation framework that maps the multiscale mechanistic effects of mutations. Built upon the Human Protein Structurome, which incorporates the 3D structures of every protein and the binding interfaces of all known protein interactions, NetFlow3D integrates atomic, residue, protein and network-level information: It clusters mutations on 3D protein structures to identify driver mutations and propagates their impacts anisotropically across the protein interaction network, guided by the involved interaction interfaces, to reveal systems-level impacts. Applied to 33 cancer types, NetFlow3D identifies 2 times more 3D clusters and incorporates 8 times more proteins in significantly interconnected network modules compared to traditional methods.